Restoration of tropical dry forest: an analysis of constraints and successes across a highly threatened biome - Mesa-Sierra, Natalia; de la Peña-Domene, Marinés; Campo, Julio; Giardina, Christian P. (Frontiers in Environmental Science, 2025)
The tropical dry forest (TDF) biome has undergone a diversity of severe disturbances, with resulting transformations and continued pressures making this biome type one of the Earth’s most threatened. Supporting large numbers of native, often endemic species, fragments of TDF serve as important but precarious refugia. There are global efforts to restore this once extensive forest type, but the impact of TDF restoration on biodiversity and ecosystem function is poorly understood. Here, we present results from an analysis of 187 unique studies, published between January 1990 and February 2020, that examined a range of TDF restoration practices. We used a meta-analytical approach to compare survival, growth, and measures of ecosystem function in restored systems and either intact reference baselines or impacted controls. Understanding that social factors can represent over-riding constraints on restoration implementation or success, we also examined human dimensions variables, which were the least evaluated metrics in our review. We found that the survival of native species plantings showed high variability within and across regions and treatments – indicating a broad need for refined restoration prescriptions to better match practice to species and site. Synthesizing a global dataset provides insights needed to increase the success of TDF restoration.